Radiation Proctitis and Management Strategies - Dushyant Singh Dahiya; Asim Kichloo; Faiz Tuma; Michael Albosta; Farah Wani (Korean Society of Gastrointestinal Endoscopy, 2022)
Radiotherapy (RT) is a treatment modality that uses high-energy rays or radioactive agents to generate ionizing radiation against rapidly dividing cells. The main objective of using radiation in cancer therapy is to impair or halt the division of the tumor cells. Over the past few decades, advancements in technology, the introduction of newer methods of RT, and a better understanding of the pathophysiology of cancers have enabled physicians to deliver doses of radiation that match the exact dimensions of the tumor for greater efficacy, with minimal exposure of the surrounding tissues. However, RT has numerous complications, the most common being radiation proctitis (RP). It is characterized by damage to the rectal epithelium by secondary ionizing radiation. Based on the onset of signs and symptoms, post-radiotherapy RP can be classified as acute or chronic, each with varying levels of severity and complication rates. The treatment options available for RP are limited, with most of the data on treatment available from case reports or small studies. Here, we describe the types of RT used in modern-day medicine and radiation-mediated tissue injury. We have primarily focused on the classification, epidemiology, pathogenesis, clinical features, treatment strategies, complications, and prognosis of RP.